Investigação do processo de aprendizagem de cálculo num curso de engenharia florestal: o uso do software Winplot na aplicação de unidades de ensino potencialmente significativas - Mendes, Felipe (2019)
Due to the difficulties presented by undergraduate students in Engineering in the disciplines of the exact areas, many theories and methodologies have been sought to facilitate and improve the process of teaching and learning, especially Calculus. In this search, the Theory of Meaningful Learning developed by David Ausubel emphasizes that the process of teaching learning needs to enable the learner to relate in a non-arbitrary and non-literal way the new information received with relevant aspects of their cognitive structure. In this way, this theory emphasizes that for learning to be meaningful, it is necessary then, according to Moreira (2012): the material to be learned is potentially meaningful for the learner, that is, relatable (or incorporable) to their cognitive structure. non-arbitrary and non-literal (substantive) form, and yet the learner must manifest a predisposition to relate the new material in a substantive and non-arbitrary way to its knowledge structure. We also have that information and communication technologies need to be constantly embedded in the learning process as tools that can help make the proposed material potentially meaningful to the student. Thus, the research work was aimed at investigating some problem situations and elaborating teaching activities that are potentially meaningful and that will provide a meaningful learning in some contents of the discipline of Calculus I. It was given focus on how the process occurs of Potentially Meaningful Teaching Unit (PMTU) of the Course of Calculus I aided by the use of Winplot Software in a graduation course in Forest Engineering. It is observed in the results obtained that the use of the PMTU allied to the use of computer software or applications of mobile communication devices (such as tablets or smartphones) can favor the occurrence of meaningful student learning. And this meaningful learning promoted by the PMTU enables students to retain in their cognitive structures the main concepts of the contents studied, and this is due to the graphical analysis of the characteristics and properties of the functions represented in the cartesian plane of the software used during the studies in classroom.